Variable Findings for Drug‐Induced Sleep Endoscopy in Obstructive Sleep Apnea with Propofol versus Dexmedetomidine. (26th January 2016) - Capasso, Robson; Rosa, Talita; Tsou, David Yung‐An; Nekhendzy, Vladimir; Drover, David; Collins, Jeremy; Zaghi, Soroush; Camacho, Macario
Abstract : Objective: To compare VOTE classification findings (velum, oropharyngeal‐lateral walls, tongue base, and epiglottis) for drug‐induced sleep endoscopy (DISE) among patients with obstructive sleep apnea (OSA) using 2 sedation protocols. Study Design: Case series with chart review. Setting: Single tertiary institution. Subjects: Patients with OSA who underwent DISE. Methods: A total of 216 patients underwent DISE between November 23, 2011, and May 1, 2015. DISE findings based on VOTE classification were compared between patients receiving the propofol‐ and dexmedetomidine‐based sedation protocols. Results: Patients with OSA (N = 216; age, 44.3 ± 11.7 years; body mass index, 27.9 ± 4.8 kg/m 2 ) underwent DISE with intravenous administration of propofol (n = 52) or dexmedetomidine (n = 164). There were no statistically significant differences between the 2 groups in baseline apnea‐hypopnea index, oxygen desaturation index, Mallampati score, tonsil size, Epworth Sleepiness Scale score, peripheral oxygen saturation nadir, age, sex, or body mass index. Patients in the propofol group had a significantly increased likelihood of demonstrating complete tongue base obstruction (75%, 39 of 52) versus partial or no obstruction (25%, 13 of 52) in the anterior‐posterior dimension, as compared with the dexmedetomidine group (complete obstruction: 42.7%, 70 of 164; partial or no obstruction: 57.3%, 94 of 164; odds ratio: 4.0; 95% confidence interval: 2.0‐8.1; P =. 0001). Obstruction of other airway subsites was not significantly different. Conclusion: Use of propofol versus dexmedetomidine to induce sedation may have a significant effect on the pattern of upper airway obstruction observed during DISE. Randomized prospective studies are indicated to confirm these initial findings.